2022
DOI: 10.3389/feart.2022.844969
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Surface Deformation Caused by Excavation of Curved Shield in Upper Soft and Lower Hard Soil

Abstract: Existing studies on surface deformation prediction consider single soil layers and straight-line excavation when investigating deformation caused by metro shield construction. In this study, we provide a new prediction method for studying the soil deformation caused by curved shield tunnel construction in the upper soft and lower hard soil. The deformation equations are derived using the Mindlin solution and random medium theory and are verified using engineering examples and numerical simulation. The influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Jia and Gao [14] derived displacement equations based on random medium theory to access the deformation rules of curved shield tunnels during adjacent excavations. Deng et al [5] improved the extent of over-excavation losses and the form of the contour distribution deeply, meanwhile, they proposed the prediction formula for surface settlement by using the mirror theory [41] and Mindlin's solution [33], involving the effects of over-excavation and uneven loading.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jia and Gao [14] derived displacement equations based on random medium theory to access the deformation rules of curved shield tunnels during adjacent excavations. Deng et al [5] improved the extent of over-excavation losses and the form of the contour distribution deeply, meanwhile, they proposed the prediction formula for surface settlement by using the mirror theory [41] and Mindlin's solution [33], involving the effects of over-excavation and uneven loading.…”
Section: Introductionmentioning
confidence: 99%
“…The principles of straight-line tunnel excavation inducing deformation of adjacent ground and pre-existing structures are fairly well established and further influence the field of small curvature tunnels. So far, the methods, used in predicting the ground movement, stress and response of adjacent structures due to shield tunneling along small radius curved route, are classified into three categories, including numerical simulations [14,21,30,45,48,52,55,51], on-site monitoring methods [7,39,52,58], and analytical methods [5,7,14,22,23,40]. In numerical simulation applications and researches, Zhang et al [55] suggested that inclined excavation loading could have an effect on the structural response and surface settlement produced by shield tunnels with different curvature radii.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past two decades, numerous tunnels have been successfully constructed (Wang et al, 2022a;Zhou et al, 2022;Wang et al, 2023a). The shield tunneling technology, known for its safety and efficiency, has been extensively utilized in the construction of urban subways and municipal tunnels (Langmaack and Lee, 2016;Xu et al, 2020;Jia and Gao, 2022). However, when a shield machine traverses clayey strata, the excavated clayey muck tends to adhere to the cutter head and cutters (Hollmann and Thewes, 2013;Wang et al, 2023b;Gao et al, 2023).…”
Section: Introductionmentioning
confidence: 99%